PENGARUH LINGKUNGAN SEKOLAH DAN KEFEKTIFAN BELAJAR TERHADAP PRESTASI BELAJAR IPS DI SD KIP MACCINI - Alannasir, wahyullah; Selvi, Nurhayati (STKIP Andi Matappa Pangkep, 2019)
This study aims to determine (i) the influence of the school environment on social studies learning outcomes; (ii) the effect of learning effectiveness on social studies learning outcomes; and (iii) the joint effect of the school environment and the effectiveness of learning on social studies learning outcomes at Maccini KIP Elementary School. Ex post facto research method. Questionnaire data collection techniques. The population is all students of Maccini KIP elementary school consisting of 12 classes. The sampling technique used was multistage random sampling to obtain 113 students. Data analysis techniques are descriptive and inferential. The results showed that the school environment of the school did not have a significant influence on students' social studies learning outcomes at SD KIP Maccini. The effectiveness of learning has a significant effect on students' social studies learning outcomes at Maccini KIP Elementary School. This shows that if the effectiveness of learning is high then student learning outcomes are also high. The school environment and the effectiveness of joint learning have a significant effect on students' social studies learning outcomes at SD KIP Maccini. This shows that the interaction between the school environment and the effectiveness of learning will show high student learning outcomes.